EXPLORING STUDENTS’ LEARNING EXPERIENCES IN SCHOOL PODCASTING PROGRAM AS AN ALTERNATIVE MEDIA FOR SPEAKING PRACTICE - FARIZAH, NIJMATUL; KUSWARDANI, RAHAYU (SEAQIL Journal of Language Education, 2024)
The objectives of this study are to explore the students’ learning experience before, during, and after producing a podcast. This study has been conducted at secondary school in Surabaya. The researchers employed a qualitative descriptive which involved five students who participated in the school podcasting program. Data was collected through a semi-structured interview consisting of 20 questions. The result from the study showed that the school podcasting program provided students with novel experiences which let them fully engaged in a productive activity. It helped them to provide a real practice of their speaking skills in English language. It also showed that topics selected for the podcast were their interests which was helpful for the students to contribute positively in giving out opinions expressively and enriched the content of the conversation become more attractive. Students created scripts, collaborated with friends in producing the podcast, and reflected on the experiences meaningfully. The activities in preparing a podcast and aired it, helped the students to perform better in speaking and gained more confidence through hands-on experience. Thus, a school podcasting program could be the appropriate activity to assist students in speaking practice through real conversation facilitated through podcast as a selected social media. The results of this study provided teachers with a broader insight into how to discover and create an effective activity and media to improve students' speaking skills by integrating technology into the learning process.